Tinjauan Literatur: Peran Jahe dan Kombinasi Herbal dalam Meningkatkan Produksi ASI pada Ibu Menyusui - Kusumaningsih, Meilia Rahmawati; Putri, Dhini Yunizar (Jurnal Midwifery, 2026)
Introduction: Every mother has high hopes of being able to breastfeed her baby exclusively, but failure to provide exclusive breastfeeding often leaves mothers disappointed. Blocked milk ducts, breast swelling, sore nipples, mastitis, and breast abscesses are common problems in the first two weeks of postpartum. The purpose of this article is to examine the role of ginger and herbal combinations in increasing breast milk production in breastfeeding mothers. Method: This article was written using a literature review design with article searches using Google Scholar (8 articles) and PubMed (2 articles). Result: Ginger contains galactagogues that can increase breast milk production and anti-inflammatory compounds such as gingerol, shogaol, and zingerone, which can soothe and reduce pain. The use of medicinal plants varies from region to region, so ginger combinations vary. Consuming ginger or its combination has no side effects. However, side effects such as diarrhea, nausea, yellow stools, and skin rashes can occur with ginger and turmeric formulations. Conclusion: Ginger plays a role in increasing breast milk production and the combination of ginger also contains ingredients that help increase breast milk production so that combining ginger with other herbs can increase breast milk production more significantly than giving ginger alone.